Optimalisasi Lahan Sempit Menggunakan Hidroponik Pakcoy Dengan Pemanfaatan Botol Bekas Di Lingkungan 02 Kelurahan Bumi Agung Kecamatan Kalianda - Samosir, Meyline; Indrawan W, M. Fadly; Aidil Azra, Rafael; Aulia Syahdani, Fitri; Aulia Rahma, Syafira; Cinta Hafidah Zalma, Aura; Khairunisa, Dinda; Sarida, Munti (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The main problem faced by Neighborhood 02, Kelurahan Bumi Agung, is the dense residential land conditions and the high plastic bottle waste due to mineral water consumption. Despite this, the community shows great interest in agriculture, as evidenced by the many potted plants in their yards. Based on this, KKN Bumi Agung students implemented a hydroponic program based on plastic bottle waste as a solution to optimize the use of narrow land and reduce plastic waste. This program was implemented on January 23, 2025 at the Bumi Agung KKN Post with socialization and training methods attended by 17 residents. The training included techniques for seeding and planting pakcoy using a simple and affordable passive hydroponic system. Residents showed great enthusiasm in learning various aspects of hydroponics, from the types of plants that can be cultivated to alternative nutrients such as Liquid Organic Fertilizer (POC). The program successfully created a sustainable farming system on limited land and provided a solution for plastic waste management, supporting the creation of a cleaner and healthier environment in Bumi Agung Village.